Students Who are Listening to Classical Music during Anatomic Identification Test Have Lower Stress Level - Istadi, Yani (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2018)
Introduction: Just like any other test, anatomical identification test can also cause high stress. Classical music intervention has proven effective in mitigating stress level in clinical context. However, whether or not it is effective as well to reduce stress level during anatomical identification test remains unknown.Objective: discovering whether listening to classical music can alleviate stress level in students when attending anatomical identification examination.Methods: Experimental research with post-test only control group design, involving 148 students as its sample obtained using proportionate stratified random sampling. The sample is divided into 2 groups: the group who listen to classical music and the one who did not listen to classical music. The stress level was measured using Visual Analogue Scale (VAS). The data are analyzed using Chi Square test.Results: Students who do not listen to classical music are mostly experiencing moderate (33 students or 22.29%), mild (29 students or 19.59%) and severe (12 students or 8.1%) stresses. On the other hand, students who listen to classical music are mostly experiencing mild (44 students or 29.72%), moderate (29 students 19.59%) and severe (1 student or 0.67%) stresses. The Chi Square test shows significant difference,Â  p= 0.002.Conclusion: Listening to classical music makes students have lower stress level when attending anatomical identification test.